2023
DOI: 10.1108/jdqs-11-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying preferences for ESG investments: evidence from an emerging market

Abstract: This paper aims to examine the time-varying preferences for environment, social and corporate governance (ESG) investing in an emerging market. The investors seek ESG-conscious investments during a positive economic outlook, reflecting the time-varying nature of ESG demand. Specifically, the author shows that high-ESG stocks have negative abnormal returns during bad economic times but turn into positive abnormal returns in good economic times. The author also suggests that the alpha spread between high-ESG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Others suggest that no clear linear relationship exists between ESG performance and corporate value (Filbeck and Gorman, 2004). Cho (2023) suggested that high-ESG stocks yield negative abnormal returns in economic downturns in the South Korean stock market. Harabida et al (2022) and Asteriou et al (2023) noted that highly-rated ESG firms posted more pronounced negative abnormal returns than lower-rated ESG firms during COVID-19 in European markets.…”
Section: Esg and Firm Valuementioning
confidence: 99%
“…Others suggest that no clear linear relationship exists between ESG performance and corporate value (Filbeck and Gorman, 2004). Cho (2023) suggested that high-ESG stocks yield negative abnormal returns in economic downturns in the South Korean stock market. Harabida et al (2022) and Asteriou et al (2023) noted that highly-rated ESG firms posted more pronounced negative abnormal returns than lower-rated ESG firms during COVID-19 in European markets.…”
Section: Esg and Firm Valuementioning
confidence: 99%
“…Buallay (2018) evidenciou que países da União Europeia buscaram estabelecer e implementar relatórios de sustentabilidade com o intuito de fortalecer relações com a sociedade em geral e as comunidades empresariais, avançando na sustentabilidade. Cho (2023), ao avaliar as variáveis de ESG em um mercado emergente, identificou que ações com alto ESG apresentam retornos anormais negativos em tempos de recessão, mas se transformam em anormais positivos em tempos econômicos bons.…”
Section: Conselho De Administração E Desempenho Esgunclassified
“…It has gained global recognition in recent decades because ESG investing strives to unite financial aspirations with positive societal and environmental impacts. Advocates of this approach believe that companies proficient in managing ESG aspects exhibit greater sustainability and resilience over extended periods [3]. By taking ESG factors into account, investors can pinpoint businesses that are not only financially stable but also make beneficial contributions to society while mitigating potential risks associated with inadequate environmental or social practices [4].…”
Section: Introductionmentioning
confidence: 99%
“…Companies with strong ESG performance can attract a broader pool of investors, including those who prioritize sustainability. This access to capital can support growth initiatives and foster positive change [3,5].…”
Section: Introductionmentioning
confidence: 99%